Analysis of Teacher Strategies in Learning to Overcome Bullying Behavior and Increase Tolerance of Grade IV Students at SDN 108 Moncongloe - Suryadi M., Nova Anjarsari; Setiawan, Ince Prabu; Hastati, Sri (EduLine: Journal of Education and Learning Innovation, 2025)
This study aims to analyze the strategies used by teachers in learning to overcome bullying and increase tolerance in fourth-grade students and identify supporting and inhibiting factors in their implementation. This type of research is a case study, using a descriptive qualitative approach with fourth-grade teachers, principals, and fourth-grade students as subjects. Data were obtained through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results show that teacher strategies in overcoming bullying include being a role model, providing advice, and internalizing character values. Meanwhile, strategies in building student tolerance are carried out through group work, collaborative activities, and habituating respect for differences. The findings of this study reveal that school institutional support, parental involvement, and a conducive school climate are factors for success, while time constraints and heterogeneity of student backgrounds are the main obstacles.